Risk factors and barriers to implementation of breastfeeding: Review (2018)
Breastfeeding ensures adequate nutrition during the early stages of child development, because multiple and unsurpassed properties, which is why it has a great impact on world public health; Despite this recognition, there are difficulties that hinder its normal course and even produce its abandonment. In order to establish strategies that can boost breastfeeding rates such as duration and exclusivity, it is imperative to identify the challenges that breastfeeding support groups must assume, when they are intervening in the promotion and management of the most frequent problems described in the literature. After an exhaustive review of 55 studies published in the last five years, strategies for prevention and control of the main problems associated with breastfeeding were identified, as well as the impact of this on the decrease of the short-term and long term morbidity and mortality rate. In the promotion, proteccion and and support of breastfeeding, 3 main public policies are described: infant and young child feeding, child-friendly hospitals and the marketing law of breast milk substitutes. This is how the results show the importance of carrying out advocacy interventions through adequate transfer of information and addressing the usual problems during breastfeeding through support groups in order to improve practices and thus prevent and solve possible potential problems present during this stage. © 2018 Asociacion Espanola de Dietistas-Nutricionistas. All Rights Reserved.